2012
DOI: 10.1097/mpg.0b013e31823a8a4c
|View full text |Cite
|
Sign up to set email alerts
|

Stool Pattern Changes in Toddlers Consuming a Follow‐on Formula Supplemented With Polydextrose and Galactooligosaccharides

Abstract: Healthy 9- to 48-month-old children (n = 133) were randomized to receive a cow's-milk-based follow-on formula (control) or the same formula with polydextrose and galactooligosaccharides (PDX/GOS) for 108 days. Pediatricians assessed diarrheal disease, stool pattern, acute respiratory infection, systemic antibiotic use, and growth. The 2 groups had similar weight-for-length/height z score and similar odds of having diarrheal disease, acute respiratory infection, and systemic antibiotic use; however, PDX/GOS had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 16 publications
2
24
1
Order By: Relevance
“…In addition, infants fed the GOS-containing formula showed higher prevalence of loose faeces and fewer formed/soft faeces than the infants in the control group. Other researchers have also described the softening of faeces in infants fed formulas containing GOS [ 13 ], GOS/FOS [ 4 , 35 ], GOS/FOS/pectin acidic-oligosaccharides (pAOS) [ 36 ] or GOS/PDX [ 30 , 37 ]. This effect is potentially beneficial in reducing the hard faeces of formula-fed infants and is probably a result of the osmotic stimulation caused by SCFAs during the fermentation of GOS by colonic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, infants fed the GOS-containing formula showed higher prevalence of loose faeces and fewer formed/soft faeces than the infants in the control group. Other researchers have also described the softening of faeces in infants fed formulas containing GOS [ 13 ], GOS/FOS [ 4 , 35 ], GOS/FOS/pectin acidic-oligosaccharides (pAOS) [ 36 ] or GOS/PDX [ 30 , 37 ]. This effect is potentially beneficial in reducing the hard faeces of formula-fed infants and is probably a result of the osmotic stimulation caused by SCFAs during the fermentation of GOS by colonic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Arslanoglu et al performed a double-blind placebo-controlled study including 259 newborns with parental history of atopic disease who were randomized to the feeding with either a formula supplemented with scGOS/lcFOS 8 g/L or regular formula. Similarly, Ribeiro et al, who performed an RCT study on 133 9-to 48-month-old children randomized to standard follow-on formula (control) or the same formula with polydextrose and galactooligosaccharides (PDX/GOS) for 108 days, did not find a difference between the two groups in the amount of diarrheal disease, acute respiratory infection, and systemic antibiotic use (Ribeiro et al, 2012). Although the differences in the number of upper respiratory tract infection and infections requiring antibiotic treatment were not statistically significant (P = 0.07, P = 0.10, respectively), the cumulative incidence of recurring infections and recurring respiratory infections were significantly lower in the prebiotic than in the control group (3.9% vs. 13.5% and 2.9% vs. 9.6%, respectively; P < 0.05).…”
Section: Protection Against Infections and Treatment Of Acute Diarrheamentioning
confidence: 95%
“…The high concentration of particles may cause osmotic retention of liquids in the intestine, which results in an increase in the humidity and volume of intestinal contents. In the majority of clinical studies regarding the effects of supplementation of infant formulas with prebiotics, increased frequency of defecation and/or softer consistency of stools more similar to that of the breast-fed than standard formula-fed children were observed (Holscher et al, 2012;Veereman-Wauters et al, 2011;Westerbeek et al, 2011;Vivatvakin et al, 2010;Bisceglia et al, 2009;Ziegler et al, 2007;Ashley et al, 2012;Williams et al, 2014;Ribeiro et al, 2012;Rao et al, 2009). Increase of fecal bolus leads to intestinal distention, stimulating peristalsis, fecal humidity, and acidity, as well as potential hormonal effects resulting in increased intestinal motility.…”
Section: Gastrointestinal Transit and Resorption Of Nutrientsmentioning
confidence: 99%
“…As far as growth was concerned, none of the studies showed a significant difference between the supplemented and non-supplemented group. [6][7][8][9][10][11][12]16,19,20,[28][29][30][31] However, several limitations should be considered: first of all, the role model for ideal infant growth is not the formula-fed but the breast-fed infant; moreover, none of those studies assessed long-term prebiotic effect on infant growth.…”
Section: Discussionmentioning
confidence: 99%